2017
DOI: 10.1080/09658211.2017.1414848
|View full text |Cite
|
Sign up to set email alerts
|

Temporal grouping effects in musical short-term memory

Abstract: Recent theoretical accounts of verbal and visuo-spatial short-term memory (STM) have proposed the existence of domain-general mechanisms for the maintenance of serial order information. These accounts are based on the observation of similar behavioural effects across several modalities, such as temporal grouping effects. Across two experiments, the present study aimed at extending these findings, by exploring a STM modality that has received little interest so far, STM for musical information. Given its inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 69 publications
(164 reference statements)
3
9
0
Order By: Relevance
“…Primacy and recency effects have been observed for STM recall or recognition of tone sequences (Gorin, Mengal, & Majerus, 2017;Greene & Samuel, 1986;Mondor & Morin, 2004). Also, there is some indication that in musical reproduction tasks, serial order transpositions may follow similar transposition gradients as is observed in verbal and visuospatial STM tasks (Mathias, Pfordresher, & Palmer, 2015).…”
mentioning
confidence: 87%
“…Primacy and recency effects have been observed for STM recall or recognition of tone sequences (Gorin, Mengal, & Majerus, 2017;Greene & Samuel, 1986;Mondor & Morin, 2004). Also, there is some indication that in musical reproduction tasks, serial order transpositions may follow similar transposition gradients as is observed in verbal and visuospatial STM tasks (Mathias, Pfordresher, & Palmer, 2015).…”
mentioning
confidence: 87%
“…Based on the observed pattern of correlations between the different tasks, we decided to regroup the tasks as a function of verbal item, musical item, and domain-general serial order STM components (see the Results section for more details). Note that the formation of a domain-general order component is also supported by empirical evidence supporting the view that the processing of serial order information in verbal and musical domains of STM involves similar mechanisms (Gorin et al, 2016, 2018b, 2018a). The construction of the composite scores was based on a data-driven approach and was done in order to reduce the complexity of the subsequent set of regression analyses.…”
Section: Methodsmentioning
confidence: 54%
“…These tasks are characterized by patterns of serial order errors which are similar to those observed in verbal STM tasks (Mathias, Pfordresher, & Palmer, 2015), such as transposition gradients, and transposition errors involving items of distant serial positions but sharing the same metrical signature which resemble interposition errors observed in the verbal domain (Henson, 1996). Also, in studies conducted on non-musician participants, we recently showed that musical STM for serial order is characterized by similar ordering effects as those witnessed in verbal STM tasks (Gorin, Mengal, & Majerus, 2018b, 2018a), as well as a by a similar sensitivity to timing-based interference (Gorin et al, 2016). This raises the question of the existence of cross-modal serial order STM mechanisms.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Several serial order effects considered as benchmark phenomena in the verbal STM domain (Hurlstone et al, 2014;Lewandowsky & Farrell, 2008) have also been observed in a recent series of musical STM experiments (Gorin, Kowialiewski, & Majerus, 2016;Gorin et al, 2018a;Gorin, Mengal, & Majerus, 2018b). The authors interpreted these results as evidence for the existence of domain-general processes to represent serial order information in the musical domain.…”
mentioning
confidence: 68%